Density of states approach to dense quantum systems - Biagio Lucini (Physical Review D, 2014)
We develop a first-principle generalized density-of-states method for numerically studying quantum field theories with a complex action. As a proof of concept, we show that with our approach we can numerically solve the strong sign problem of the Z3 spin model at finite density. Our results are confirmed by standard simulations of the theory dual to the considered model, which is free from a sign problem. Our method opens new perspectives on ab initio simulations of cold dense quantum systems, and in particular of Yang-Mills theories with matter at finite densities, for which Monte Carlo-based importance sampling is unable to produce sufficiently accurate results.